Entrepreneurship research: a bibliometric study of the ENANPADs 1997-2008 - Ferreira, Manuel Portugal (2010)
We have witnessed a fast growth in academic interest on entrepreneurship over the past two to three decades, although at disparate paces in different countries. A wealth of papers presented and published, books, dedicated journals, websites, professional and research groups have emerged accompanying this increased interest. It is thus important to understand what are these scholars studying. In this paper we examine the state of the art in entrepreneurship research in Brazil, by scrutinizing the entire track record of the papers presented at the EnANPAD over a twelve years period: 1997 -to 2008. The results of the bibliometric analysis revealed that entrepreneurship research maintains a broad spectrum of interests, focusing both on contextual, individual and process issues. Less visible is a unified theoretical background or the use of established theories foundational to other management disciplines. It is notable the increase in Brazilian entrepreneurship research, both empiric, theoretical and casestudy based. We conclude with an umbrella discussion and suggestions for future research.